ATRESIA DUODENAL, DIAGNOSIS AND TREATMENT - I Dewa Ayu Widiastuti; I Made Darmajaya (Universitas Udayana, 2013)
Duodenal atresia is a condition where the duodenum is not well developed. Atresia Duodenal is an obstruction that often occur in the neonate after birth. Atresia occurs in 1 of 1000 births. Intestinal Atresia may occur at various places in the small intestine. 50% of cases of intestinal atresia occurs in the duodenum. Symptoms are often caused the bowel obstruction. Symptoms will appear within 24 hours after birth. Continuous vomiting are the most frequent symptoms. If the child's condition is not treated quickly, the child will experience dehydration, weight loss, electrolyte balance disorders. If dehydration is not treated, it can happen or hipokloremia hypokalemic metabolic alkalosis. On physical examination found abdominal distension. Investigations at the prenatal period by using prenatal ultrasonography. Investigations that postnatal use a x-ray. X-ray examination of the first by the plain abdominal x-ray. X-ray image shows the double-bubble sign without gas in the distal colon. Management options include menagement preoperative, intraoperative and postoperative management. Life expectancy for infants with duodenal atresia which is 90-95%. Mortality is high due to prematurity and multiple congenital abnormalities.